1999
DOI: 10.1029/1998ja900167
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the auroral acceleration region as observed by FAST

Abstract: Abstract. The Fast Auroral Snapshot (FAST) explorer satellite was designed to investigate the microscale structure of the auroral acceleration region that was unresolved by previous satellites. This paper will present highlights from the first 2 years of the FAST mission and compare them with previous observations and auroral models. In particular, we find good agreement with the overall field-aligned current systems previously discovered; however, we present evidence that the downward currents are often carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 73 publications
13
127
0
Order By: Relevance
“…The connection between double layers and electron holes is known since the very early simulations of double layers [Singh, 1982;Singh and Schunk, 1982a, 1982b, 1984Singh et al, 1987], including the plateauing of the DL-accelerated electron beams by the plasma turbulence mainly consisting of the electron holes Thiemann, 1980a, 1980b]. This connection was eventually confirmed by satellite observations both in the upward and downward current regions [Carlson et al, 1998;Ergun et al, 1998;McFadden et al, 1999]. However, rarer observations of electron holes in the auroral upward current region (AUCR) compared to the auroral downward current region (ADCR) remains a mystery.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…The connection between double layers and electron holes is known since the very early simulations of double layers [Singh, 1982;Singh and Schunk, 1982a, 1982b, 1984Singh et al, 1987], including the plateauing of the DL-accelerated electron beams by the plasma turbulence mainly consisting of the electron holes Thiemann, 1980a, 1980b]. This connection was eventually confirmed by satellite observations both in the upward and downward current regions [Carlson et al, 1998;Ergun et al, 1998;McFadden et al, 1999]. However, rarer observations of electron holes in the auroral upward current region (AUCR) compared to the auroral downward current region (ADCR) remains a mystery.…”
Section: Introductionmentioning
confidence: 51%
“…Using magnetic conjunction between the Cluster satellites and DMSP, Vaivads et al [2003] reported that as the Cluster satellites 1, 2 and 3 crossed the auroral arc a density enhancement was found at 4.7R e geocentric altitude while at the low altitude of DMSP (∼800 km) an extended density cavity was found. While the formation of the lowaltitude density cavity is well known from satellites like FAST [McFadden et al, 1999], the density enhancement measurements at high altitude, perhaps in the source region of the auroral arcs, is an unexplained new finding. Our simulation discussed here reveals this feature of the density at high altitudes in an auroral potential structure associated with an arc.…”
Section: Potential and Density Structures Of The Moving V-shaped Doubmentioning
confidence: 99%
See 2 more Smart Citations
“…In the region of upward field-aligned currents, parallel electric fields (which energize plasma sheet electrons to produce the aurora) accelerate ion beams out of the ionosphere and also reflect low-energy electrons, trapping them between the potential structure and their low-altitude mirror points. FAST satellite measurements have shown that the dominant contribution to the electron density in the density cavities associated with ion beams is energetic plasma sheet electrons [Strangeway et al, 1998;McFadden et al, 1999]. Outside these regions, measurements from the S3-3 Langmuir probe [Kletzing et al, 1998] show that the electron density is primarily due to electrons with energies of a fraction of an eV (ionospheric electrons).…”
Section: Discussionmentioning
confidence: 99%